“Peace” in the Quran Text: a Look at the Significance and Purports (The Verbal Noun as a Model) | (السّلام في النّص القرآنيّ: نظرات في الدّلالة والمقاصد (المصدر نموذجًا - Nahla Alshalabi; Tar Abdallahi (Al-Zahra : Journal for Islamic and Arabic Studies, 2019)
The study aims to determine the singificance and purport of the use of the verbal noun (سلام peace) given the linguistic kinship between language and style in the context of the Qur'anic discourse.We discovered that the diversity of the purports of the word "peace" is based on the context in which it is presented, and the general atmosphere that embraces it. Peace in Quran generaly means the spread of safety and stability among individuals and societies.But, some linguistic contextual factors might convey another meaning, and due to the central position of the concept of peace in the Qur'an, the word peace has formed through its contextual occurance a collocational range either by addition or apposition.